2020
DOI: 10.17794/rgn.2020.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Ore Texture on the Bond Work Index at the Mahd Ad Dahab Gold Mine: A Case Study

Abstract: The grinding process in industrial ball mills is the basic unit and most energy-consuming component. Therefore, great economic gains will be achieved if a slight improvement occurs in the efficiency of grinding. The variation of gold ore petrography affects its mechanical properties which in turn, affects the grinding process. In this investigation, different gold-bearing ore types from the Mahd Ad Dahab gold mine were tested. As a part of the current study, some of the mechanical and physical properties inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…The relationships between petrographical and mechanical properties of rocks have been investigated in several studies [2,3,21,22,23,24]. The rock mechanics and crushability tests are frequently used in the simulation and modelling of the processes occurring in the comminution equipment, and they can be used in the studies of the relationship between rock properties and grindability [25].…”
Section: Relationship Between Petrographical Properties and The Crushmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationships between petrographical and mechanical properties of rocks have been investigated in several studies [2,3,21,22,23,24]. The rock mechanics and crushability tests are frequently used in the simulation and modelling of the processes occurring in the comminution equipment, and they can be used in the studies of the relationship between rock properties and grindability [25].…”
Section: Relationship Between Petrographical Properties and The Crushmentioning
confidence: 99%
“…Several authors have investigated the relationship between the Bond-work index (Wi,B) and the rock texture. Abdelhaffez [22] has reported that the overall mineralogy itself has little effect on the Wi,B. The presence of secondary sulphate minerals, the difference in the hardness of the sulphate minerals, but mostly the degree of cohesion of the ore minerals with the enclosing gangue minerals and the variation in the composition of the gangue minerals plays an important factor in the mineral processing.…”
Section: Relationship Between Petrographical Properties and The Crushmentioning
confidence: 99%
“…One of these studies examined the failure of fractured rocks under uniaxial compression, which resulted in the spread of the first micro fractures over a wide shear band, as well as the coalescence of micro fractures into a critical shear failure zone, which resulted in limited testing of this failure. At elevated confining pressures, the Elastic moduli and peak strength values of rock increase, and the deformation passes from fragile to spermatogenesis [1]- [3]. Numerous studies have shown that particle size is crucial, because it is used to identify the mechanical behavior of rock samples of the same composition.…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between petrological and mechanical properties of rocks have been investigated by numerous authors [1,2]. The mechanical properties are mainly influenced by the mineral association, their distribution, shape, size, orientation or in other words the texture and the degree of alteration, cracks, and porosity.…”
Section: Introductionmentioning
confidence: 99%